Social Media Alcohol Marketing and Its Impact on Young People’s Alcohol Use: A Comparison between India and Australia - Gupta, Himanshu (Curtin University, 2018)
A cross-national comparison of 1) marketing strategies used by leading Indian and Australian alcohol brands on their official social media (SM) pages and 2) the association between exposure to SM alcohol marketing and alcohol use among young Indians and Australians, was conducted. Results suggest that alcohol companies tailor strategies to specific national contexts to engage users with these strategies. Significant associations were identified between alcohol-related content posted on SM and young people’s alcohol use.